Educational Planning in the Digital Age: A Systematic Literature Review - Khasanah, Zuiati (PPSDP International Journal of Education, 2025)
Educational planning is undergoing a profound transformation as digital technologies reshape policy design, institutional governance, and learning ecosystems. This systematic literature review aims to synthesize current scholarly evidence on how digital transformation influences educational planning processes and outcomes. Using a qualitative meta-synthesis approach, fifteen peer-reviewed international articles published between 2019 and 2025 were analyzed thematically. The findings reveal four dominant dimensions shaping educational planning in the digital age: data-driven decision-making and governance, technology integration in pedagogy, infrastructure and equity challenges, and digital leadership and capacity building. The review demonstrates that digitalization enhances planning precision, responsiveness, and inclusivity through real-time data analytics, flexible learning models, and cross-sector collaboration. However, persistent challenges remain, including digital inequality between regions, ethical concerns related to data use, and limited teacher preparedness. The novelty of this review lies in its integrative synthesis of fragmented empirical findings into a coherent conceptual framework that connects digital governance, pedagogical innovation, and human capacity development. Practically, the findings offer strategic insights for policymakers, school leaders, and educators in designing adaptive, ethical, and inclusive educational planning models. Overall, this review provides a synthesized conceptual framework and identifies critical directions for future research on sustainable and human-centered educational planning in the digital era.